The Mediating Effect of Acculturation Ability in the Relationship between Discriminatory Stress and Mental Well-Being among Chinese Students in South Korean Universities - Zhang, Yizhen (Transactions on Social Science, Education and Humanities Research, 2024)
As the number of international students in Korea increases, it is particularly important to pay attention to their mental well-being and adaptability. This study aimed to explore the mediating effect of acculturation ability on the relationship between discrimination stress and mental well-being among Chinese students studying in Korea. The mental well-being of international students has always been a concern. However, for the Chinese students in Korea, who occupy the largest proportion of international students and have special discrimination stress, their psychological adaptation to the cross-cultural environment has not been fully studied. Discrimination stress may negatively affect their mental well-being, and the acculturation ability may play a key role in this process. This study examined the relationship between discrimination stress, acculturation ability, and mental well-being by reviewing data from the literature on Chinese international students studying in South Korea. This study discovered that the association between discriminatory stress and mental well-being is significantly mediated by acculturation skills. That is, international students with higher acculturation ability are more likely to mitigate the adverse effects of discrimination experiences on their mental well-being. The results of this study highlight the importance of acculturation ability in the mental well-being research of international students. In the future, support and intervention measures should be developed for Chinese students studying in South Korea to improve their acculturation ability so as to reduce the negative impact of the stress brought by discrimination on mental well-being and promote the sound development of cross-cultural education.